2020
DOI: 10.3390/plants9030383
|View full text |Cite
|
Sign up to set email alerts
|

The Regulatory Effects of a Formulation of Cinnamomum osmophloeum Kaneh and Taiwanofungus camphoratus on Metabolic Syndrome and the Gut Microbiome

Abstract: The number of people with metabolic syndrome (MetS) is increasing year by year, and MetS is associated with gut microbiota dysbiosis. The demand for health supplements to treat or prevent MetS is also growing. Cinnamomum osmophloeum Kaneh (CO) and Taiwanofungus camphoratus (TC) are endemic to Taiwan. Both have been shown to improve the symptoms of MetS, such as dyslipidemia and hyperglycemia. Herein, we investigated the effect of CO, TC and their formulations on diet-induced obese mice. Male C57BL/6J mice were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Additionally, certain plants show potential in improving kidney function ( Owis et al, 2017 ), regulating glucose and fatty acid metabolism ( Reshidan et al, 2019 ), and balancing lipoprotein secretion and energy homeostasis ( Singh et al, 2017 ). Furthermore, some plants demonstrate the ability to restore abnormal blood glucose regulation and rebalance intestinal microbiota ( Wang et al, 2020 ), thus presenting multifaceted approaches to addressing metabolic syndrome.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, certain plants show potential in improving kidney function ( Owis et al, 2017 ), regulating glucose and fatty acid metabolism ( Reshidan et al, 2019 ), and balancing lipoprotein secretion and energy homeostasis ( Singh et al, 2017 ). Furthermore, some plants demonstrate the ability to restore abnormal blood glucose regulation and rebalance intestinal microbiota ( Wang et al, 2020 ), thus presenting multifaceted approaches to addressing metabolic syndrome.…”
Section: Resultsmentioning
confidence: 99%
“…It is also reported that solid-state cultured AC can reduce hyperglycemia and tend to alleviate metabolic disorder in HFD-induced obese mice, mainly reduce the relative abundance of Firmicutes-to-Bacteroidetes ratio and elevate the relative abundance of Akkermansia spp. ( Wang et al, 2020 ). The arrangement of the enterocyte was not disrupted by AC extract treatment, but intactness and denseness of hepatic tissue was elevated by regulating redox and cytoskeleton-related proteins and increasing the abundance of Akkermansia spp.…”
Section: Potential With the Gut-microbiome-brain Axis Of Acmentioning
confidence: 99%
“…It is also reported that solid-state cultured AC can reduce hyperglycemia and tend to alleviate metabolic disorder in HFD-induced obese mice, mainly reduce the relative abundance of Firmicutes-to-Bacteroidetes ratio and elevate the relative abundance of Akkermansia spp. (Wang et al, 2020).…”
Section: Potential With the Gut-microbiomebrain Axis Of Acmentioning
confidence: 99%
“…All data presented herein were obtained from refs. [44,54,55,70,72,74,75,78,88,95,96,98,102–111,116,119–121,124–130,132,134–137,140–144,147–156,158,159,161,163–171,173–176...…”
Section: Diet Composition and Exposure Timementioning
confidence: 99%